Population norms for the AQoL derived from the 2007 Australian National Survey of Mental Health and Wellbeing - Graeme Hawthorne; Sam Korn; Jeff Richardson (Elsevier, 2013)
Abstract Objective : To provide Australian health‐related quality of life (HRQoL) population norms, based on utility scores from the Assessment of Quality of Life (AQoL) measure, a participant‐reported outcomes (PRO) instrument. Methods: The data were from the 2007 National Survey of Mental Health and Wellbeing. AQoL scores were analysed by age cohorts, gender, other demographic characteristics, and mental and physical health variables. Results: The AQoL utility score mean was 0.81 (95%CI 0.81-0.82), and 47% obtained scores indicating a very high HRQoL (>0.90). HRQoL gently declined by age group, with older adults' scores indicating lower HRQoL. Based on effect sizes (ESs), there were small losses in HRQoL associated with other demographic variables (e.g. by lack of labour force participation, ESmedian: 0.27). Those with current mental health syndromes reported moderate losses in HRQoL (ESmedian: 0.64), while those with physical health conditions generally also reported moderate losses in HRQoL (ESmedian: 0.41). Conclusions: This study has provided contemporary Australian population norms for HRQoL that may be used by researchers as indicators allowing interpretation and estimation of population health (e.g. estimation of the burden of disease), cross comparison between studies, the identification of health inequalities, and to provide benchmarks for health care interventions.